استراتيجية الدولة الجزائرية المنادية بدعم القطاع الخاص ودعم مسؤوليته الإجتماعية ، مدخل محوري للنهوض بالتنمية المحلية المستدامة بالدولة. - رجب, لطيفة; بن خديجة, منصف (جامعة الوادي - University of Eloued, 2021)
سلّطت الورقة البحثية الضوء على الدور الرائد الذي يلعبه القطاع الخاص بإحداث وإنجاح التنمية المحلية المنشودة بالدولة، ولأن هذه التنمية ترتكز على عدة أبعاد من أهمها البعد الاقتصادي، الاجتماعي والبيئي أو ما يعرف بالتنمية المحلية المستدامة من جهة، ومن جهة أخرى فقد أثبتت عدة دراسات ميدانية (غربية وعربية) أن تبني مفهوم المسؤولية الاجتماعية الذي انتشر وبشكل واسع يُعد مدخل محوري لدعم استدامة التنمية المحلية للدولة وعليه فقد هدفت الدراسة البحثية بداية إلى الوقوف على أهمية أجهزة الدولة المسخرة لخدمة وتنويع نشاط القطاع الخاص بها. وكتكملة لدعم هذا القطاع الاساسي فقد بادرت الدولة إلى خلق استراتيجيات وآليات تُعنى بالتحسيس بأهمية تبني فلسفة المسؤولية الاجتماعية بالقطاع الخاص، ليتمكن هذا الأخير من المساهمة وفق ضوابط المسؤولية الاجتماعية في إحداث التنمية المحلية المستدامة بالدولة. وتوصلت دراستنا لمجموعة نتائج تعكس بمجملها أهمية تعزيز أطر دمج المسؤولية الاجتماعية بالقطاع الخاص (الأطر التشريعية والتنظيمية)، وإشراك منظم لجميع أطراف التنمية المحلية، بالتكثيف من حملات التحسيس بأهمية هذا المفهوم لدى القطاع الخاص أو العام، بهدف توعية الاطراف المسؤولة والفاعلة بهذا القطاع المحوري بأهمية تبنيهم لهذه الفلسفة الاجتماعية، والانعكاسات الايجابية التي سيجنيها إثر تبنيه لها، ومن جهة أخرى الانعكاسات التي ستجنيها الدولة من خلال التنمية المحلية المستدامة التي سيسهم في تحققها بدوره. The research paper shed light on the private sector to bring about local development in the state, and because development is based on several dimensions, the most important of which is the economic, social and environmental dimension or what is known as sustainable local development, and on the other hand, several studies (Western and Arab) have proven that the concept of social responsibility that has spread widely It is a pivotal entrance to support the sustainability of the local development of the country.The research study aimed at examining the importance of state agencies involved in serving the private sector. As a supplement to support the sector, the state initiated to create strategies and mechanisms concerned with sensitizing the importance of adopting social responsibility in the private sector, in order to be able to contribute in accordance with the regulations of social responsibility in creating sustainable local development in the country. The reached a set of results that reflect the importance of promoting the inclusion of social responsibility in the private sector (legislative and regulatory frameworks ...), and the involvement of all local development parties in intensifying awareness campaigns of the importance of the concept in the private or public sector, with the aim of educating the parties responsible in the pivotal sector of the importance of their adoption of social philosophy, and the positive repercussions That it will gain from its adoption of it, as well as the repercussions that the country will gain through sustainable local development will achieve for it
The strategy of the state Of Algeria calling for supporting social responsibility in the private sector, A pivotal entrance to support its sustainable development.
مقال
Keywords: مسؤولية اجتماعيه ; قطاع خاص ; تنمية محلية مستدامة ; تنمية اقتصاديه